Study on the performance of anaerobic inverse fluidized bed reactor: Effects of fluidization velocity and hydraulic retention time on hydrogen production via dark fermentation - Yufei Fu; Yangfan Song; Hongwei Chen; Ao Lei; Yetao Zhang; Yongqiang Li; Le Luo (Biomass and Bioenergy, 2027)

Traction mechanism and parameter optimization of curved grousers based on coupled DEM–MBD - Fu Zhang; Le Yang; Yubo Qiu; Yakun Zhang; Zhidan Zhong; Sanling Fu (Journal of Terramechanics, 2027)

Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

Additional records of Late Devonian seed plants in South China - Deming Wang; Min Qin; Peng Xu; Yi Zhou; Le Liu; Pu Huang; Qiang Fu; Yuehan Pan (Review of Palaeobotany and Palynology, 2026)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

O2 enhanced SF6 degradation in SiO2@TiO2 filled dielectric barrier discharge - Yalong Li; Zhe Huang; Kun Wan; Yangjing Le; Mingli Fu; Ying Zhang; Zhaodi Yang; Yan Luo; Xiaoxing Zhang (Journal of Environmental Chemical Engineering, 2026)

Temperature effects on dissolved organic matter release and plant growth from aged microplastics of different particle sizes - Xin Zhang; Wei Chu; Jiabao Ma; Le Fu; Zhiqi Yang; Xiuping Li; Fei Yu; Jie Ma (Journal of Environmental Chemical Engineering, 2026)

Advanced phase-change cooling strategies for high-power electronics: A comprehensive review of engineered fluids, surfaces, and system integrations - Hailing Fu; Mengqi Yu; Yu Liu; Wenjie Qiu; Hao Li; Kunyang Jiang; Zihan Chen; Le Yu; Wenjing Zhang (International Journal of Refrigeration, 2026)

Balancing N₂O and NH₃ emissions with maize yield: Investigating the role of alternate drip irrigation and 3,4-dimethylpyrazole phosphate (DMPP) - Junming Liu; Yuanyuan Fu; Le Yang; Zhuanyun Si; Sunusi Amin Abubakar; Huijie Li; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Bingcheng Si; Yang Gao; et al. (Soil and Tillage Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Comparative effects of sodium butyrate and Artemisia seed polysaccharide on performance, and glucagon-like peptide-2 in post-weaning Ordos fine wool sheep lambs - Ding Yang; Xinshuai Bing; Lu Jin; Chunhua Zhang; Xiangxiong Zhang; Shengli Li; Chula Sa; Le Fu; Wenting Li; Haizhou Sun (Small Ruminant Research, 2026)

Analysis, isolation and anti-tumour activity of the alkaloids from Ceratocarpus arenarius L - Aimulaguli Kuerban; Hanghang Fu; Yanni Ma; Dongyu Lei; Xingyu Ren; Lu Jin; Le Pan (Natural Product Research, 2026)

Design and evaluation of bio-inspired track shoes for improved traction and mobility in complex topography - Fu Zhang; Le Yang; Xinyue Wang; Yakun Zhang; Yumei Liu; Sanling Fu (Soil and Tillage Research, 2026)

Ultrasonic-assisted suppression and transformation of by-products for efficient sodium stannate synthesis - Dongbin Wang; Tian Wang; Wenlong Miao; Mingge Fu; Liuxin Xiang; Thiquynhxuan Le; Libo Zhang (Process Safety and Environmental Protection, 2026)

Mechanistic insight into the ultrasonic-enhanced H2O2 advanced oxidation of refractory COD from molybdenum smelting waste acid under extreme acidity - Liuxin Xiang; Tao Xu; Qian Zhang; Tian Wang; Mingge Fu; Wenlong Miao; Thiquynhxuan Le; Libo Zhang (Journal of Water Process Engineering, 2026)

Symmetry-mismatch-guided topological evolution in pore-space-partitioned metal-organic frameworks for enhanced ethylene purification - Zhang-Lei Zhong; Chen-Chen Xing; Yan-Yu Zhang; Ai-Ming Zhang; Le-Wei Zheng; Yu Wang; Wenyu Yuan; Ying Wang; Shun-Fu Du; Quan-Guo Zhai (Chemical Engineering Journal, 2026)

Relapsing Seronegative Immune-Mediated Cerebellar Ataxia with Evolving Intrathecal Immune Activation and Rituximab Consolidation in a Toddler: A Case Report - Panhui Yu; Fang Chen; Weixiu Wang; Jingjie Li; Liyao Ma; Pengjiu Fu; Yifan Zhao; Le Wang (The Cerebellum, 2026)

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

Uncertainty analysis of contaminant sources in fracture networks: A framework integrating falsification and Bayesian evidential learning - Kehan Miao; Yong Huang; Le Zhang; Liming Guo; Zhimin Fu; Thomas Hermans (Advances in Water Resources, 2026)

Can protected area networks effectively conserve ecosystem services at the landscape scale? Evidence from Wuyishan Biodiversity Priority Conservation Area, China - Tianqi Fu; Yue Cao; Siren Lan; Le Yu; Lingyun Liao (Ecosystem Services, 2026)

Enhanced SO2F2 degradation via Fe2O3-based catalyst coupled with DBD plasma - Yalong Li; Zhaodi Yang; Xiaoxing Zhang; Mingli Fu; Yangjing Le; Lei Yu; Huiyu Tan; Zhe Huang; Zhongfeng Wang (Journal of Cleaner Production, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Insight into the meat quality differences of Tibetan sheep from different altitudes based on metabolomics - Ruisi Liu; Jianing Fu; Shaobo Li; Minghui Gu; Liang Li; Le Xu; Jiangying Yu; Dequan Zhang; Li Chen (Food Chemistry, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Silencing of SOX4 prevents endothelial injury from ox-LDL stimulation by inhibiting NF-κB pathway and ferroptosis - Le-Wei He; Pan Hou; Wen-Bo Fu (Tissue and Cell, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

Pig welfare in scientific literature from 1991 to 2024: A text mining approach - Lianlian Fu; Yu Le (Journal of Veterinary Behavior, 2026)

Metal sulfide-based electrocatalysts for water splitting: From rational design to advanced applications - Yi Liu; Yijun Wu; Xiantuo Chen; Yongmin Ying; Jili Wen; Huanan Wang; Le Chen; Yingsu Qu; Min Li; Jiang Wu; Zaiguo Fu (Fuel, 2026)

Construction and temporal external validation of interpretable machine-learning models for predicting tigecycline-associated hypofibrinogenemia - An Fu; Daihong Guo; Man Zhu; Le Cai; Ao Gao; Liqiang Cui (European Journal of Clinical Pharmacology, 2026)

Strengthening Connections in Observing the North Atlantic Meridional Overturning Circulation: Outcomes from a Joint RAPID-OSNAP Workshop - Nicholas Foukal; Isabela Le Bras; Yao Fu; Tillys Petit; Tiago Biló; Shane Elipot; Ben Moat (Oceanography, 2026)
The Atlantic Meridional Overturning Circulation (AMOC) redistributes heat, salt, oxygen, carbon, and nutrients in the Atlantic Ocean, providing warmth and moisture to the climate of northern Europe (Rhines and Häkkinen, 2003), displacing the Intertropical Convergence Zone northward of the equator (Ben-Yami et al., 2024), sequestering anthropogenic carbon in the deep ocean (Brown et al., 2021), and seeding the subpolar North Atlantic with sufficient nutrients to support the annual spring phytoplankton bloom (Williams et al., 2026). While models and proxies of the AMOC have been instrumental in understanding its past and future variability, large inter-model differences necessitate direct observations to provide a baseline from which to compare the models, as well as an unambiguous time series of recent AMOC variability. However, measuring a system as large and complex as the AMOC presents many challenges: spanning thousands of kilometers horizontally and covering full ocean depths, the AMOC is composed of currents that vary on daily to millennial time scales. Recirculating flows that can be an order of magnitude stronger than the AMOC itself further complicate observations.

Congo Basin Carbon Cycle Responses to Global Change - Sarah Worden; Rong Fu; A. Anthony Bloom; Marijn Bauters; Hans Verbeeck; Temilola Fatoyinbo; Wannes Hubau; Lydie‐Stella Koutika; Steve Kwatcho Kengdo; Sybryn L. Maes; Vincent Medjibe; Nicholas J. Russo; et al. (Global Change Biology, 2026)
The Congo Basin and its contiguous forests harbor globally significant carbon stocks, estimated at 65 gigatons of C (GtC) above and belowground. Despite rising temperatures and intensifying droughts, they have remained a carbon sink, albeit weak: 0.26–0.50 GtC yr. −1 carbon uptake since 1980. However, these forests' carbon stocks and fluxes, including gross primary productivity, respiration, net primary productivity, and riverine carbon transport, remain poorly quantified. This limits understanding of the region's role in the global carbon cycle, its vulnerability to environmental change, and its potential as a long‐term carbon sink. We review and quantify Congo Basin and contiguous forest carbon stocks and fluxes and synthesize the current knowledge on how key global change drivers shape the region's carbon cycle. We find limited responses to long‐term precipitation variability, but declining stocks and fluxes in response to long‐term and increasing temperature and drought frequency. Land cover and land use changes, largely driven by small‐scale agriculture, logging, and agro‐industrial expansion, reduce carbon stocks, ecosystem structure and functioning, and animal‐mediated ecosystem services. In contrast, large‐scale savanna biomass burning delivers phosphorus and nitrogen to Congo Basin forests via cross‐equatorial winds, providing additional nutrients and supporting carbon sequestration. In situ studies suggest that CO 2 fertilization has increased intrinsic water‐use efficiency, although its effects may be modulated by climate change, and its impacts on biomass accumulation remain uncertain. Legacy effects from historical land use and climate change likely shaped present‐day vegetation structure, yet their relative influence is unclear. High‐resolution carbon monitoring, improved remote sensing, and strengthened in situ measurement networks are needed to quantify the impacts of these key drivers and their interactions on the Central African carbon cycle. This is needed to inform conservation strategies and advance understanding of the region's future as a carbon sink under global change pressures.

Pore Structure Evolution in Marine Sands Under Laterally Constrained Axial Loading - Xia-Tao Zhang; Cheng-Liang Ji; Le-Le Liu; Hui-Long Ma; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Installation in sand is sensitive to its evolving pore structure, yet design models rarely update permeability for real-time fabric changes. This study tracks the stress-dependent pore size distribution of coarse sand under laterally constrained compression using high-resolution X-ray nano-CT. Scans taken at six axial stress levels show that the distribution shifts toward smaller radii while keeping its log-normal shape. A single shifting factor, defined as the current median radius normalized by the initial value, captures this translation. The factor decays with axial stress according to a power law, and the exponent as well as the reference pressure are calibrated from void ratio data. The resulting closed-form expression links mean effective stress to pore radius statistics without extra fitting once the compressibility constants are known. This quantitative relation between effective stress and pore size distribution has great potential to be embedded into coupled hydro-mechanical solvers, enabling engineers to refresh hydraulic permeability at every computation step, improving predictions of excess pore pressure and soil resistance during suction anchor penetration for floating wind foundations.

Investigation of Pullout Capacity Characteristics of Suction Anchors Under Inclined Loads in Layered Soil - Cheng-Liang Ji; Xia-Tao Zhang; Hao-Yu Wang; Le-Le Liu; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Suction anchors are widely used in marine engineering because of their easy installation, cost-effectiveness, and excellent load-bearing capacity. However, existing research on their bearing capacity has primarily focused on homogeneous soils, which fails to adequately reflect the actual bearing capacity of layered seabed soils. Therefore, this study conducted a series of numerical simulations to investigate the pullout bearing capacity of suction anchors subjected to inclined loads in upper-stiff–lower-soft layered clay. By considering the clay strength (Sum/kD) and soil layer thickness ratio (Th/L, Tc/L), this study systematically explores the influence of the optimal centerline loading depth (Zcl,opt), uniaxial ultimate bearing capacity (Hult and Vult), and the VH failure envelope of suction anchors. The results indicate that the layer thickness ratio Th/L of lightly overconsolidated clay (LOC) is the key factor influencing the Zcl,opt and ultimate bearing capacity Hult and Vult. An increase in Th/L significantly enhances the pullout resistance of suction anchors, which primarily results from the combined enhancement effect of lateral friction resistance and end resistance at the anchor–soil interface. The layered clay has a distinct influence on the horizontal and vertical bearing capacities of suction anchors. Based on the results of parameter analysis, a conservative analytical expression for the lower bound of the VH failure envelope curve is further proposed. The research conclusions provide a theoretical basis and engineering practice guidance for the optimized design and safety assessment of suction anchors in layered soil.

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

One-step preparation of recyclable solid acid catalysts for biodiesel synthesis - Wenlong Miao; Guang Fu; Mingge Fu; Liuxin Xiang; Tian Wang; Thiquynhxuan Le; Libo Zhang; Phan Duc Lenh (Process Safety and Environmental Protection, 2025)

Hepatocyte proteome destabilization and novel targets for PFASs unveiled through combined thermal proteome profiling and deep transfer learning - Zimeng Wu; Yue Zou; Kang Yang; Xiaomei Yu; Zhiqiang Fu; X. Chris Le; Jingwen Chen (Journal of Hazardous Materials, 2025)

Nano-thiophene-graphdiyne engineered buried interface toward homogeneous crystallization of perovskite films - Yutongyang Fu; Le Liu; Zhibin Yu; Rui Han; Yilin Chang; Yunxin Zhang; Wenfei Guo; Bin Huang; Jiajia Du; Wenfeng Yang; Tonggang Jiu (Chemical Engineering Journal, 2025)

Single-ion conductor covalently grafted onto MOFs to realize solid polymer electrolyte tripartite conducting channels in lithium metal batteries - Feixiang Zhou; Linfeng Fu; Qingping Wu; Chao Ding; Le Yu; Weidong Zhou; Fahai Cao; Hui Liu; Jun Xu (Chemical Engineering Journal, 2025)

3D Geomechanical Modeling for Sweet Spot Identification in Thin-Layer Carbonate Reservoirs - Jian Yang; Zhouyang Wang; Miao Yang; Yuanyu Yang; Xucheng Li; Le Luo; Yan Fu; Man Huang; Zhi Zhong; Dongchao Su; Zikun Li; Fulong Ning (Geotechnical and Geological Engineering, 2025)

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

Not all company is comforting: metabolic consequences of conspecific presence depend on species’ social system in fish - Cheng Fu; Daphne Cortese; Oluwaseun Ojelade; Amelia Munson; Le Gao; Shijian Fu; Lauren E. Nadler; Shaun S. Killen (Behavioral Ecology and Sociobiology, 2025)

Effect of sterically hindered amines on the cycling capacity of biphasic absorbents for industrial CO2 capture - Zanbu Geng; Le Fu; Yang Yang; Yixi Wang; Wenqing Xu; Runlong Hao; Daoping Zhan; Tingyu Zhu (Journal of Environmental Sciences, 2025)

All-round management of lead iodide toward efficient perovskite solar cells - Zhibin Yu; Le Liu; Yutongyang Fu; Yilin Chang; Jiajia Du; Zhiwei Ma; Tonggang Jiu (Chemical Engineering Journal, 2025)

High efficiency removal of oxytetracycline hydrochloride using a novel Fe/Mn co-modified biochar activated peroxymonosulfate: Synergistic effects of Fe and Mn - Le Lv; Yafeng Li; Xiangyu Fu; Qianqian Li; Jin Tang (Process Safety and Environmental Protection, 2025)

Three key steps complete the biosynthesis of phenylalanine-derived salicylic acid in diverse plant species - Kaihuai Li; Le Luo; Huan Chen; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2025)

Formation and suppression strategies of by-product in tin oxidative dissolution process - Dongbin Wang; Wenlong Miao; Mingge Fu; Vanduoc Tran; Liuxin Xiang; Tian Wang; Thiquynhxuan Le; Libo Zhang (Journal of Environmental Chemical Engineering, 2025)

Design and evaluation of bio-inspired electro-osmosis system for reducing soil adhesion on agricultural equipment - Le Yang; Zhihong Zhang; Baoping Yan; Shuo Yuan; Fu Zhang (Soil and Tillage Research, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Characteristics and life cycle carbon emission reduction potential of waste recycling after implementing new waste classification policy in China: From case study to national perspective - Hao Fu; Le Chen; Wei Fang; Wenfang Gao; Kun Hu; Panyue Zhang; Guangming Zhang (Journal of Environmental Sciences, 2025)

Improving groundwater vulnerability assessment using machine learning - Juanjuan Fu; X. Chris Le (Journal of Environmental Sciences, 2025)

The Complete Mitochondrial Genome of Acrossocheilus spinifer (Osteichthyes: Cyprinidae) and Its Phylogenetic Analysis - Jian Gong; Shi-Qi She; Guang-Fu Liu; Xing-Xing Zhao; Le-Yang Yuan; E Zhang (Fishes, 2025)
In this study, we sequenced and characterized the complete mitochondrial genome of Acorssocheilus spinifer, an endemic stream-dwelling cyprinid species from South China first described in 2006. The mitogenome is 16,591 bp in length and contains the standard set of 37 genes (13 protein-coding genes, 22 tRNA genes, 2 rRNA genes) plus a control region. The genome exhibits typical cyprinid characteristics, with most genes encoded on the H-strand and a nucleotide composition biased toward A + T (55.9%). All tRNA genes display the typical cloverleaf secondary structure, except for tRNASer (GCU), which lacks the dihydrouridine (DHU) arm. Phylogenetic analysis using complete mitogenomes from 14 Acrossocheilus species revealed that 12 species form a monophyletic assemblage with three distinct clades. Within this framework, A. spinifer clusters closely with A. beijiangensis, supporting previous morphological observations. Our findings provide valuable genetic data for further taxonomic refinement and conservation efforts for Chinese barred species of Cyprinidae.

Significant contribution of urban morphological diversity to urban surface thermal heterogeneity - Jiyao Zhao; Le Yu; Lei Zhao; Haohuan Fu; Peng Gong (Urban Climate, 2025)

Chinese cities show disparity trends in carbon efficiency: A hybrid approach combining explainable machine learning and econometrics - Le Ma; Tong Cheng; Longgang Xiang; Chao Wang; Liyuan Wei; Jianing Wang; Chaoya Dang; Wenjie Fu; Huayi Wu (Sustainable Cities and Society, 2025)

New maps of mafic mineral abundances in global mare units on the Moon - Yuzhen Wang; Haijun Cao; Jian Chen; Changqing Liu; Xuejin Lu; Chengxiang Yin; Xiaohui Fu; Le Qiao; Guang Zhang; Chengbao Liu; Peng Zhang; Zongcheng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effect of hazelnut protein oxidation on O/W emulsion stability, interfacial properties and lipid oxidation based on hazelnut protein oxidation - Ziyi Huang; Yanyan Wu; Le Chen; Hongyu Jiang; Chuan Tian; Miao Fu; Chunmao Lyu (Journal of Stored Products Research, 2025)

Evaluation of quality characteristics of hazelnut using infrared assisted enzymatic peeling technology - Le Chen; Ziyi Huang; Yanyan Wu; Hongyu Jiang; Chuan Tian; Miao Fu; Chunmao Lyu (Food Control, 2025)

Asymmetric influence of urban morphology changes on land surface temperature between daytime and nighttime - Jiyao Zhao; Le Yu; Lei Zhao; Haohuan Fu; Peng Gong (Sustainable Cities and Society, 2025)

Effect of chlorine dioxide (ClO2) combined with different oxygen permeability package treatments on postharvest antioxidant activity and storage life of ‘Liaofeng’ grapes - Yanyan Wu; Le Chen; Ziyi Huang; Chuan Tian; Hongyu Jiang; Miao Fu; Chunmao Lyu (Food Control, 2025)

Low-temperature oxidative pyrolysis characteristics of tobacco components - Zhongya Guo; Ke Zhang; Huanwei Li; Lili Fu; Qi Zhang; Ze Liu; Le Wang; Xueyi Qiao; Heng Guo; Ran Chen; Bing Wang; Bin Li (Biomass and Bioenergy, 2025)

Evaluating overhanging slope failure mechanisms and rockfall trajectories through integrated UAV imagery and discrete element modeling - Meng-Chia Weng; Geng-Man Zhang; Yu-Yao Fu; Hoang-Khanh Le; Yu-Hui Kao (Landslides, 2025)
To evaluate the threat of rockfall from an overhanging slope above a bridge, this study proposes a comprehensive analysis procedure to assess the failure mechanisms of the slope and the associated rockfall trajectories. The analysis utilizes high-resolution point cloud data obtained through integrated UAV-based imagery technology, enabling a detailed evaluation of joint configurations and slope stability. The geometric reconstruction of unstable rock blocks, combined with stereographic projections, provides an in-depth analysis of potential failure modes. Discrete element modeling (DEM) is employed to simulate the failure processes and predict rockfall trajectories, with particular emphasis on the potential risks to the underlying bridge. The results indicate that rockfall events near the bridge are primarily driven by wedge-shaped failures, a finding confirmed by both the proposed inverted three-dimensional projection method and DEM simulations. The analysis identifies critical rock blocks near the bridge, underscoring the need for targeted mitigation strategies. This case study demonstrates the effectiveness of integrating UAV-derived data with DEM for assessing overhanging slope failures and managing rockfall risks in similar geological settings.

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Mn and P co-doped biochar catalyst for persulfate efficient degradation of tetracycline hydrochloride：Process and mechanism - Xiangyu Fu; Yafeng Li; Keqing Cui; Yihan Liu; Le Lv (Journal of Environmental Chemical Engineering, 2024)

Construction of ultra-smooth and void-free buried interface via bilateral chemical bridging for efficient and hysteresis-suppressed perovskite solar cells - Yao Yao; Fushen Lu; Zhibin Yu; Qinglin Du; Jiajia Du; Yilin Chang; Zhiwei Ma; Yutongyang Fu; Yu Li; Le Liu; Tonggang Jiu (Chemical Engineering Journal, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Lead specifically declines tyrosine hydroxylase activity to induce the onset of Parkinson's disease through disrupting dopamine biosynthesis in fly models - Yue Niu; Yifan Pan; Yaqi Wang; Yongqi Fu; Zhangwu Zhao; Le Kang (Environmental Pollution, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Activation of GPR30 Ameliorates Cerebral Ischemia–Reperfusion Injury by Suppressing Ferroptosis Through Nrf2/GPX4 Signaling Pathway - Yong-qiang Zhang; Ting Sun; Zhen Zhao; Jing Fu; Le Yang; Yuan Xu; Jing-feng Zhao; Xiu-ling Tang; An Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

Geologic context of Chang'e-6 candidate landing regions and potential non-mare materials in the returned samples - Ziyi Jia; Jian Chen; Jiaqi Kong; Le Qiao; Xiaohui Fu; Zongcheng Ling (Icarus, 2024)

Corrigendum to “Technological challenges and future perspectives of plant-based meat analogues: From the viewpoint of proteins” [Food Res. Int. 186 (2024) 114351] - Tianyu Su; Bei Le; Wei Zhang; Kathrine H. Bak; Philip O. Soladoye; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Food Research International, 2024)

Technological challenges and future perspectives of plant-based meat analogues: From the viewpoint of proteins - Tianyu Su; Bei Le; Wei Zhang; Kathrine H. Bak; Philip O. Soladoye; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Food Research International, 2024)

A novel chain-like conjugated donor-π-acceptor molecular additive for highly efficient and stable perovskite solar cells - Haipeng Jiang; Chunyu Wei; Jin Wang; He Dong; Xinmin Fu; Le Zhang; Fengyou Wang; Lin Fan; Maobin Wei; Huilian Liu; Lili Yang; Yongsheng Yan (Chemical Engineering Journal, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Biased technological progress and coordination of carbon emission reduction and haze reduction - Jiachao Peng; Ming Yi; Shuke Fu; Hui Wang; Le Wen; Teng Wang (Environmental Science and Pollution Research, 2024)

Evaluation of weak genotoxicity of hydroxychloroquine in human TK6 cells - Xilin Li; Yuan Le; Yuxi Li; Si Chen; Lei Guo; Xin Fu; Mugimane G. Manjanatha; Nan Mei (Toxicology Letters, 2024)

Particle swarm optimization for Rayleigh wave frequency-velocity spectrum inversion - Zhao Le; Xianhai Song; Xueqiang Zhang; Chao Shen; Hanbing Ai; Shichuan Yuan; Daiguang Fu (Journal of Applied Geophysics, 2024)

Spectral adjustable Re-Cs3Cu2I5 nanocrystal-in-glass composite with long-term stability - Qihua Yang; Hanqi Wei; Guihua Li; Shujuan Zhao; Yuchen Ao; Xuan Liu; Le Fu; Gemei Cai (Chemical Engineering Journal, 2024)

Mitochondrial Regulation of Macrophages in Innate Immunity and Diverse Roles of Macrophages During Cochlear Inflammation - Yuan Zhang; Fanglei Ye; Xiaolong Fu; Shen Li; Le Wang; Yutian Chen; Hongmin Li; Shaojuan Hao; Kun Zhao; Qi Feng; Peipei Li (Neuroscience Bulletin, 2024)

Land use/cover and land degradation across the Eurasian steppe: Dynamics, patterns and driving factors - Zhenrong Du; Le Yu; Xin Chen; Bingbo Gao; Jianyu Yang; Haohuan Fu; Peng Gong (Science of The Total Environment, 2024)

Synthesis, crystal structures, and biological activity of aroylhydrazone di-m-chlorobenzyltin complexes - Wujiu Jiang; Pengfei Zhou; Le Chen; Weiwei Fu; Yuxing Tan (JBIC Journal of Biological Inorganic Chemistry, 2023)

Upcycling spent lithium battery cathodes into efficient PMS catalysts for organic contaminants degradation - Lei Xu; Le Liang; Chen Chen; Ze-Hang Chen; Zong-Bin Lv; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2023)

Effects of light regimes and benthic fish disturbance on the foraging behavior of Vallisneria natans in heterogeneous sediments - Hong Su; Mingfan Li; Chao Wang; Guanbao Fu; Ruijie Le; Gang Sun (Environmental Science and Pollution Research, 2023)

LncRNA activates immune response against Vibrio anguillarum in the intestine-liver axis of turbot (Scophthalmus maximus L.) by sponging miRNA in a ceRNA regulatory network - Xin Cai; Chengbin Gao; Alan J. Lymbery; Le Ma; Qiang Fu; Ranran Huang; Chao Li (Aquaculture, 2023)

Numerical simulations of seawater spraying on launch platform during CZ-8X offshore launching - Yifei Su; Xuxin Lu; Guigao Le; Guanghua Li; Benshuai Fu (Advances in Space Research, 2023)

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

Light-driven sustainable enhancement of Cr(VI) reduction via the combination of Cr(VI)-reducing bacteria, Paraclostridium bifermentans with CdS nanoparticles - Yilin Le; Xing He; Mengnan Liu; Xue Liu; Shidong Zhou; Rongrong Xie; Yu Fu; Huilei Wang; Jianzhong Sun (Journal of Environmental Chemical Engineering, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Ocean Circulation from Space - Rosemary Morrow; Lee-Lueng Fu; Marie-Héléne Rio; Richard Ray; Pierre Prandi; Pierre-Yves Le Traon; Jérôme Benveniste (Surveys in Geophysics, 2023)
This paper reviews the recent progress in our estimation of ocean dynamic topography and the derived surface geostrophic currents, mainly based on multiple nadir radar altimeter missions. These altimetric observations provide the cornerstone of our ocean circulation observing system from space. The largest signal in sea surface topography is from the mean surface dominated by the marine geoid, and we will discuss recent progress in observing the mean ocean circulation from altimetry, once the geoid and other corrections have been estimated and removed. We then address the recent advances in our observations of the large-scale and mesoscale ocean circulation from space, and the particular challenges and opportunities for new observations in the polar regions. The active research in the ocean barotropic tides and internal tidal circulation is also presented. The paper also addresses how our networks of global multi-satellite and in situ observations are being combined and assimilated to characterize the four-dimensional ocean circulation, for climate research and ocean forecasting systems. For the future of ocean circulation from space, the need for continuity of our current observing system is crucial, and we discuss the exciting enhancement to come with global wide-swath altimetry, the extension into the coastal and high-latitude regions, and proposals for direct total surface current satellites in the 2030 period.

Molybdenum cycling in Andean-type subduction and metallogenic implications - Wei Mao; Hong Zhong; Jiehua Yang; Liang Liu; Yazhou Fu; Xingchun Zhang; Jie Li; Le Zhang; Haifeng Fan; Yanwen Tang; Xiaocui Chen (Mineralium Deposita, 2023)

Seasonal variation characteristics of atmospheric peroxyacetyl nitrate (PAN) and its source apportionment in a megacity in southern China - Shi-Yong Xia; Xiao-Feng Huang; Zhi-Jie Li; Nan Fu; Zhen Jiang; Li-Ming Cao; Le-Wei Zeng; Guang-He Yu (Science of The Total Environment, 2023)

A new quasi-static friction model for the spherical hinge bearing in structural engineering - Le Chen; Xin Ruan; Xiaonong Guo; Wei Chen; Lilei Fu (Engineering Structures, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Cadmium stimulated cooperation between bacterial endophytes and plant intrinsic detoxification mechanism in Lonicera japonica thunb - Mengdi Xie; Xiaoyu Gao; Saiwei Zhang; Xiaohua Fu; Yiquan Le; Lei Wang (Chemosphere, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Mixed-linker MOFs-derived cross-linked copolymer electrolyte enables high lithium mobility for dendrite-free all-solid-state batteries - Jia Zhou; Xingfa Zeng; Linna Dong; Liya Chen; Xiangrong Wei; Yang liu; Liyi Shi; Le Yu; Jifang Fu (Chemical Engineering Journal, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Effects of benthic fish and light regimes on water quality and the growth of Vallisneria natans with two sediment types - Hong Su; Wenhui Zheng; Mingfan Li; Chao Wang; Guanbao Fu; Ruijie Le; Gang Sun (Environmental Science and Pollution Research, 2023)

Effects of radio frequency thawing on the quality characteristics of frozen mutton - Yanan Sun; Yiming Jia; Mingxia Song; Yan Liu; Le Xin; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Food and Bioproducts Processing, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Constructing macroscopic core@shell catalyst to boost tandem catalysis of methanol to aromatic - Qian Ma; Tingjun Fu; Le Yin; Zhong Li (Chemical Engineering Journal, 2023)

Surveying coconut trees using high-resolution satellite imagery in remote atolls of the Pacific Ocean - Juepeng Zheng; Shuai Yuan; Wenzhao Wu; Weijia Li; Le Yu; Haohuan Fu; David Coomes (Remote Sensing of Environment, 2023)

Resource use efficiencies, environmental footprints and net ecosystem economic benefit of direct-seeded double-season rice in central China - Xing Yu; Le Xu; Shen Yuan; Guodong Yang; Hongshun Xiang; Yifan Fu; Jianliang Huang; Shaobing Peng (Journal of Cleaner Production, 2023)

Development of species-specific PCR detection for three Mycogone species causing wet bubble disease in white button mushroom - Niu-Niu Shi; Hong-Chun Ruan; Wen-Le Chen; Qiao-Hong Chen; Fu-Ru Chen; Yi-Xin Du (Crop Protection, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Continuous-flow membrane bioreactor enhances enrichment and culture of autotrophic nitrifying bacteria by removing extracellular free organic carbon - Xiaodi Zhao; Yi Zhang; Le Chen; Saiwei Zhang; Xiaohua Fu; Lei Wang (Environmental Science and Pollution Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Evolution stage, spatial and temporal variabilities of granite landforms in the Mount Wugongshan in Jiangxi Province of South China - Le Chai; Cun-di Zhong; Fu-sheng Guo; Xin-shu Huang; Dao-ying Wang; Chong-jian Shao; Liu-qin Chen (Journal of Mountain Science, 2022)

Surrogate Models in Rock and Soil Mechanics: Integrating Numerical Modeling and Machine Learning - J. K. Furtney; C. Thielsen; W. Fu; R. Le Goc (Rock Mechanics and Rock Engineering, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Integration of complete ensemble empirical mode decomposition with deep long short-term memory model for particulate matter concentration prediction - Minglei Fu; Caowei Le; Tingchao Fan; Ryhor Prakapovich; Dmytro Manko; Oleh Dmytrenko; Dmytro Lande; Shamsuddin Shahid; Zaher Mundher Yaseen (Environmental Science and Pollution Research, 2021)

Estrogen prevents cellular senescence and bone loss through Usp10-dependent p53 degradation in osteocytes and osteoblasts: the role of estrogen in bone cell senescence - Yu Wei; Jiayao Fu; Wenjing Wu; Pengfei Ma; Le Ren; Junhua Wu (Cell and Tissue Research, 2021)

Integration of RNA‐seq and RNAi reveals the contribution of znuA gene to the pathogenicity of Pseudomonas plecoglossicida and to the immune response of Epinephelus coioides - Le He; Luying Wang; Lingmin Zhao; Zhixia Zhuang; Xiaoru Wang; Huabin Huang; Qi Fu; Lixing Huang; Yingxue Qin; Pan Wang; Qingpi Yan (Journal of Fish Diseases, 2021)
Pseudomonas plecoglossicida is an important pathogen in aquaculture and causes serious economic losses. Our previous study indicated that znuA gene might play an important role in the pathogenicity of P. plecoglossicida . Five shRNAs were designed and synthesized to silence the znuA gene of P. plecoglossicida . Two of the five mutants of P. plecoglossicida exhibited significant reduction in the expression level of znuA mRNA with different efficiencies. The mutant with the highest silencing efficiency of 89.2% was chosen for further studies. Intrapleural injection of the znuA ‐RNAi strain at a dose of 10 5 cfu/fish did not cause the death of Epinephelus coioides , and no significant signs were observed at the spleen surface of infected E. coioides , while the counterpart E. coioides infected by the same dose of wild‐type strain of P. plecoglossicida all died in 5 days post‐infection (dpi). The expression of znuA gene of znuA ‐RNAi strain in E. coioides was always lower than that in wild‐type strain of P. plecoglossicida . The pathogen load in the early stage of infection was higher than that in the later stage of infection. Although the infection of the znuA ‐RNAi strain of P. plecoglossicida could induce the production of antibodies in E. coioides , it failed to produce a good immune protection against the infection of wild‐type strain of P. plecoglossicida . Compared with the transcriptome data of E. coioides infected by the wild‐type strain of P. plecoglossicida , the transcriptome data of E. coioides infected by the znuA ‐RNAi strain of P. plecoglossicida have altered significantly. Among them, KEGG enrichment analysis showed that the focal adhesion pathway was significantly enriched and exhibited the largest number of 302 DEMs (differentially expressed mRNAs). These results showed that the immune response of E. coioides to P. plecoglossicida infection was significantly affected by the RNAi of znuA gene.

Application of multi-component joint inversion in oil and gas exploration: A case study of reservoir and gas saturation prediction of the Xujiahe formation in the PLN area of the central Sichuan Basin - Dong Wang; Zhen-Hua He; Xu-Ben Wang; Le Li; Hai-Tao Yang; Zhi-Guo Fu; Hong-Yan Wang (Applied Geophysics, 2020)

Albian–Cenomanian A-type granite-related Ag–Pb–Zn veins in the central Yidun Terrane, SW China: constraints from the Xiasai deposit - Yan-Jun Li; Jun-Hao Wei; Jun Tan; Le-Bing Fu; Huan Li; Kun-Jia Ke (Mineralium Deposita, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Total factor productivity of cultivated land use in China under environmental constraints: temporal and spatial variations and their influencing factors - Jiachao Peng; Le Wen; Lina Fu; Ming Yi (Environmental Science and Pollution Research, 2020)

Oil palm plantation mapping from high-resolution remote sensing images using deep learning - Runmin Dong; Weijia Li; Haohuan Fu; Lin Gan; Le Yu; Juepeng Zheng; Maocai Xia (International Journal of Remote Sensing, 2020)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

An Overview of Scoring Functions Used for Protein–Ligand Interactions in Molecular Docking - Jin Li; Ailing Fu; Le Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Anti-oxidant and anti-inflammatory activities of ultrasonic-assistant extracted polyphenol-rich compounds from Sargassum muticum - Yuan Yu; Le Wang; Xiaoting Fu; Lei Wang; Xiaodan Fu; Min Yang; Zhenlian Han; Haijin Mou; You-Jin Jeon (Journal of Oceanology and Limnology, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Improving the knowledge and behavior of workplace chemical exposures in Vietnamese–American nail salon workers: a randomized controlled trial - Thu Quach; J. Von Behren; J. Tsoh; P. Reynolds; L. Fu; T. Nguyen; M. Le; T. T. Nguyen (International Archives of Occupational and Environmental Health, 2018)

Biological floating bed and bio-contact oxidation processes for landscape water treatment: simultaneous removal of Microcystis aeruginosa, TOC, nitrogen and phosphorus - Jun feng Su; Dong hui Liang; Le Fu; Li Wei; Min Ma (Environmental Science and Pollution Research, 2018)

Triptolide Promotes the Clearance of α-Synuclein by Enhancing Autophagy in Neuronal Cells - Guanzheng Hu; Xiaoli Gong; Le Wang; Mengru Liu; Yang Liu; Xia Fu; Wei Wang; Ting Zhang; Xiaomin Wang (Molecular Neurobiology, 2017)

Two New Mononuclear Copper(II)-Dipeptide Complexes of 2-(2′-Pyridyl)Benzoxazole: DNA Interaction, Antioxidation and in Vitro Cytotoxicity Studies - Qian Gan; Yongyu Qi; Yahong Xiong; Yinlian Fu; Xueyi Le (Journal of Fluorescence, 2017)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Stacked Autoencoder-based deep learning for remote-sensing image classification: a case study of African land-cover mapping - Weijia Li; Haohuan Fu; Le Yu; Peng Gong; Duole Feng; Congcong Li; Nicholas Clinton (International Journal of Remote Sensing, 2016)

Exploring the potential role of feature selection in global land-cover mapping - Le Yu; Haohuan Fu; Bo Wu; Nicolas Clinton; Peng Gong (International Journal of Remote Sensing, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Synthesis, DNA/HSA Interaction Spectroscopic Studies and In Vitro Cytotoxicity of a New Mixed Ligand Cu(II) Complex - Qian Gan; Xiabing Fu; Weijiang Chen; Yahong Xiong; Yinlian Fu; Shi Chen; Xueyi Le (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Origin of the Maoduan Pb–Zn–Mo deposit, eastern Cathaysia Block, China: geological, geochronological, geochemical, and Sr–Nd–Pb–S isotopic constraints - Yan-Jun Li; Jun-Hao Wei; Hua-Yong Chen; Jun Tan; Le-Bing Fu; Gang Wu (Mineralium Deposita, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Risk evaluation of China’s natural disaster systems: an approach based on triangular fuzzy numbers and stochastic simulation - Ju-Liang Jin; Yi-Ming Wei; Le-Le Zou; Li Liu; Juan Fu (Natural Hazards, 2012)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Eddy Dynamics From Satellite Altimetry - Lee-Lueng Fu; Dudley Chelton; Pierre-Yves Le Traon; Rosemary Morrow (Oceanography, 2010)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Sterol production and phytosterol bioconversion in two species of heterotrophic protists, Oxyrrhis marina and Gyrodinium dominans - Fu-Lin Evelyn Chu; Eric D. Lund; Paul R. Littreal; Kate E. Ruck; Ellen Harvey; Jean-René Le Coz; Yanic Marty; Jeanne Moal; Philippe Soudant (Marine Biology, 2008)

Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD - Feng Zhou; Jianmin Su; Le Fu; Yong Yang; Lineng Zhang; Liying Wang; Hongbo Zhao; Diancai Zhang; Zengxia Li; Xiliang Zha (Glycoconjugate Journal, 2008)

Designing environmental monitoring networks to measure extremes - Howard Chang; Audrey Qiuyan Fu; Nhu D. Le; James V. Zidek (Environmental and Ecological Statistics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Learning from Viruses: The Necrotic Bodies of Tumor Cells with Intracellular Synthetic dsRNA Induced Strong Anti-tumor Immune Responses - Zhengrong Cui; Uyen M. Le; Fu Qiu; Dalia S. Shaker (Pharmaceutical Research, 2007)

High-pressure/ultrahigh-pressure eclogites from the Hong’an Block, East-Central China: geochemical characterization, isotope disequilibrium and geochronological controversy - Bor-ming Jahn; Xiaochun Liu; Tzen-Fu Yui; N. Morin; M. Bouhnik-Le Coz (Contributions to Mineralogy and Petrology, 2005)

Linear transgene constructs lacking vector backbone sequences generate low-copy-number transgenic plants with simple integration patterns - Xiangdong Fu; Le Tan Duc; Stefania Fontana; Bui Ba Bong; Porntip Tinjuangjun; Durailagaraja Sudhakar; Richard M. Twyman; Paul Christou; Ajay Kohli (Transgenic Research, 2000)